Optimization of Livestock Waste Through the Production of Liquid Organic Fertilizer from Animal Feces as an Ecological Step in Kalikuning Village - Tugiyanti, Elly; Hartini, Sri; Kemala Oktasari, Sully; Mustika Sari, Astri; Wulan Utami, Wahyu; Valinka Azhari, Firsty; Sulaiman Zulfa, Nikmat (Pascasarjana Universitas Mataram, 2025)
Liquid Organic Fertilizer (LOF) is the utilization of animal fecal waste, which contains nutrients and beneficial microbes that can be applied to plants. The animal feces are mixed with EM4, which serves as a source of microbes, while molasses comes from sugar production waste and functions as food for the EM4. By doing so, mixing livestock manure with these materials and then fermenting them for 7 days allows them to be used on plants, making them more fertile. This activity is used as an ecological step to reduce environmental pollution that can cause unpleasant odors and serve as a breeding ground for disease. The activity was conducted using Participatory Rural Appraisal (PRA) through the Student Community Service Program for Community Empowerment (KKN-PMM) for farmer groups and livestock breeder groups to increase harvest yields and reduce unpleasant odors released along with animal feces. The community of Kalikuning Village, especially farmers and livestock breeders, gained knowledge about making liquid organic fertilizer to improve soil fertility for their crops. Conclusion: The community of Kalikuning Village gained new knowledge and insights into spraying liquid organic fertilizer to achieve good crop quality through the transfer of knowledge from the UNSOED KKN-PMM Team to the local residents.